Applying a social model of disability across the life span. Issue 8 (17th November 2017) - Kattari, Shanna K.; Lavery, Angela; Hasche, Leslie
ABSTRACT: With an estimated 21.3% of persons aged 15 and older experiencing disability in the USA, social workers will see clients present with disabilities across all practice settings and stages of human development. Yet, the training and terminology of social workers—which often closely aligns with medical professionals—may seem to occur in isolating silos or disciplinary theories. Social work education often views the needs of older adults and people with disabilities as two distinct populations, despite the fact that many of these individuals share similar needs for access, resources, and support. Furthermore, when discussing human development, the focus may skew to individual affective, behavioral, and cognitive processes and indicators of abnormal development and frailty. Thus, by clarifying terminology and applying a social model of disability across the life span, we identify how educational efforts related to human behavior and the social environment can promote intersectional and inclusive social work related to aging and disability.